Czar opowieści. Dylogie Catherynne M. Valente oraz Salmana Rushdiego w kontekście Księgi tysiąca i jednej nocy - Bednarek, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
From the 18th century on Arabian Nights has been influencing European imaginary, especially culture and literature. It created European vision of the Orient as well. In the 20th century popular culture gave high recognisability to many elements of Arabian Nights (such as characters: Sindbad, Aladdin or magical artefacts: a flying carpet, magic lamp). Scheherazade as an allegory for narrative art became the most important figure for scholars studying the book. The paper shows how two contemporary book cycles make intertextual links to Arabian Nights . Orphan’s Tale by Catherynne M. Valente, Harun and the Sea of stories and Luka and the fire of Life by Salman Rushdie rewrite the elements of Arabian Nights , such as characters, artefacts and linguistic allusion to the Orient. However, the narration in the works by both writers is completely different: Valente recreated a sophisticated device of narration known from the book, whereas Rushdie gave his novels a simple, linear composition. Scheherazade’s gift to spin story out of a life is needed for different aims. For Rushdie telling fairy tales is useful in writing about life of literature itself, for Valente it is important for creating an alternative to the patriarchal vision of the world.